(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The primary phenomenon is not too strong at the 1st view of preventing labor abuse. A lot of problems may be raised to solve this problem. That’s why we need to concentrate firstly in the sector of retrenchment. Because, It has a huge chain in our country. We can’t break the chain early. We need to decode the chain and need to find the hash codes of these chains. But, there are different types of nodes to face all the big issues and problems strategically. That’s why we maximum stations and networks which are we can track with some strategies by manufacturing a bridge of chain management and control system. So, we need to draw the system which can collaborate directly with the labors. In this paper, we are going to show the bridge which can zip the child labor into a folder. After that, we can extract this folder and also can treat every child very carefully. We can make up the function of GA, Blocks to reducing the problems. Four strategies of CS (Computer Science) can improvise the chain of replacement. Such as Data- set to function, function to Labor, labor to verification, and verification to control the action with the TWM method. TWM method is a completely new and impactful method that is going introduce in this paper which can improve child labor mentality. The impact of the TWM method can create also some blocks by which the block-chain method can make its implementation in the future into this topic. In fine we can say the goal and motive of this paper are to make a society that is free from child labor.